Utilization of pretreated oil palm empty fruit bunches and their hydrolysate for ethanol production by Indonesian ethanologenic yeast - SITA HERIS ANITA; MAULIDA OKTAVIANI; EUIS HERMIATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Anita SH, Oktaviani M, Hermiati E. 2023. Utilization of pretreated oil palm empty fruit bunches and their hydrolysate for ethanol production by Indonesian ethanologenic yeast. Biodiversitas 24: 5243-5252. Oil Palm Empty Fruit Bunches (OPEFB) represent a polysaccharide-rich raw material with promising potential for ethanol production. This study aimed to investigate the ethanologenic yeasts, specifically Saccharomyces cerevisiae InaCC Y93 and Kluyveromyces marxianus InaCC Y119, affect bioethanol production in three different systems: Separate Hydrolysis and Fermentation (SHF), Simultaneous Saccharification and Fermentation (SSF), and Prehydrolysis-Simultaneous Saccharification and Fermentation (PSSF). This work is distinguished by the use of indigenous Indonesian yeast strains, including a thermotolerant strain. In the pretreatment process, 1.13% oxalic acid was added to OPEFB and subjected to microwave treatment at 190°C for 3.01 min. Subsequently, cellulase enzymes (40 FPU/g) and a 10% (w/v) yeast inoculum were introduced into 5.27 g dry weight of pretreated OPEFB pulp. The OPEFB acid hydrolysate was also subjected to fermentation. Ethanol content was monitored at 24 h intervals for 72 h. The PSSF system employs K. marxianus InaCC Y119 at 48 h exhibited the highest ethanol concentration, yielding 0.290 g/g, equivalent to approximately 51.20% of the theoretical yield. Additionally, K. marxianus InaCC Y119 demonstrated its capability to ferment the OPEFB acid hydrolysate into ethanol. These findings underscore the considerable potential of K. marxianus for applications in fermenting both hexose and pentose sugars to produce ethanol within higher-temperature systems.